(untitled) (Bangladesh Journal of Zoology, 2015)
Histopathological studies of early and late stages of Epizootic Ulcerative Syndrome infected fishes from three natural ponds at Demra, Dhaka. Five different types of freshwater wild fishes such as Anabas testudineus, Channa punctatus, Colisa fasciatus, Mystus vittatus and Puntius ticto were collected from August, 2009 to December, 2010. In this study, a prevalence of 64% (322/500) was recorded. Channa punctatus was found to be the most infected fish among the examined fishes. Petechia haemorrhages and moderate necrosis with melanomacrophages and multinucleated giant cells without fungal hyphae were pronounced in the early stages in the muscles. Moderate to severe necrosis friable tissues possessing trailing fungal hyphae associated with fungal, protozoan and bacterial infection may have caused denuding or total erosion of the affected tissues. Extensive ulcers and high mortality were prominent in the late stages of infection. Cystic granulomas associated with multinucleated giant cells often engulfing fungal hyphae were the most characteristic features at the late stages in EUS affected fish. Other observations made were muscle degeneration, surrounding perforated muscle fibres and frequent degeneration of the blood vessel walls. However, the causative link between EUS and the observed histopathological features needs to be further elucidated. Bangladesh J. Zool. 43(1): 121-130, 2015